Occupational Safety in Agriculture: A Systematic Literature Review of Practices and Health Outcomes - Nugraheni, Reny; Susilo, Achmadi (International Journal of Multi Discipline Science (IJ-MDS), 2025)
This study aims to conduct a systematic review of occupational safety practices in the agricultural sector and their impact on worker health. The agricultural sector remains one of the sectors with the highest rates of workplace accidents and exposure to hazardous chemicals, especially in developing countries. Using the Systematic Literature Review (SLR) method, 21 scientific articles published in the past ten years were analyzed. The review results indicated that the use of personal protective equipment (PPE), occupational safety training, and strict regulations contribute significantly to reducing the risk of pesticide poisoning and work injuries. However, in many regions such as Indonesia, Tanzania, and Nigeria, PPE use remained low due to limited access and quality. Safety training was effective in reducing symptoms of acute poisoning, but implementation was uneven. Furthermore, chronic pesticide exposure remained a serious threat with symptoms of respiratory, neurological, and even heart disease. Studies in countries such as Iran, Colombia, and the United States showed that strong supervision and community-based education can increase risk awareness and encourage safer work behaviours. This study concluded that an integrative approach encompassing education, regulation, access to PPE, and health services was key to improving occupational safety and health in the global agricultural sector.